SERVICE QUALITY AND CUSTOMER SATISFACTION IN FURNITURE SECTOR INSTALLATION SERVICES - Kartika, Hayu; Kholil, Muhammad; Setia Bakti, Candra (Journal of Industrial Engineering & Management Research, 2020)
Abstract — This research was conducted to improve the quality of services based on customer satisfaction. There is a problem that occurs in this company is that there are still consumer complaints about the installation part services provided by this company which is around 14.6% of total sales. To reduce the percentage of complaints, it is necessary to have studies and analysis, improvements to the services provided by this company. The study uses the Service Quality (SERVQUAL) method, where the aim is to measure the level of service quality by customer expectations. The sampling technique uses non-probability sampling techniques with convenience methods. The results of this study of the twelve attributes analyzed two attributes that must be maintained the quality of service, namely B1 (Service quickly and precisely), C1 (Knowledge / Competence). And the ten attributes that must be improved and improved are the quality of services namely A1 (Timeliness of the process), A2 (Sympathetic attitude and collaboration), A3 (High service accuracy), B2 (Clarity of information), C2 (Courtesy compensation), D1 (Having understanding and knowledge of customers), D2 (Understanding customer requirements specifically), D3 (Having a comfortable operating time for customers), E1 (Equipment and equipment used (technology)), E2 (Employee appearance).